ABO Blood Group and Severity of Coronary Artery Disease Assessed by Syntax Score in Patients with Acute Myocardial (Bangladesh Heart Journal, 2022)
Introduction: As coronary artery disease (CAD) is a major cause of morbidity and mortality; timely diagnosis and appropriate therapy is of paramount importance to improve clinical outcomes. Though there are major risk factors for CAD but sometimes it does not correlate with ACS. So, search for new risk factor is necessary for better management of CAD specially STEMI. Aim: To see the association between ABO blood group and severity of CAD in patients with STEMI.Methods: This study was done during the period of January 2016 to June 2016 with STEMI at National Institute of Cardiovascular diseases, Dhaka, Bangladesh. 100 patients were grouped in I and II where group-I having 50 patients of non-O blood group and group-II having 50 patients of O blood group. After CAG all reports were analyzed by two experts and SYNTAX score were calculated and data were analyzed by SPSS.Results: Baseline characteristics (100 patients) were well matched between the groups. Low SYNTAX score (d”22) was 16% and 56%; intermediate score (23-32) was 40% and 36% and high score (>32) was 44% and 8% in group- I and group-II respectively. These indicate that patients of non-O blood group have high SYNTAX score that is more severe CAD. Univariate and multivariate regression analysis showed that non-O blood group is an independent risk factor for CAD. So easily available ABO blood grouping can be helpful to determine the severity of CAD in patients with STEMI.Bangladesh Heart Journal 2022; 37(2): 107-115